Quality of Life of Women with Breast Cancer in Radiation and Isotopes Center - Mohamed, Ghofran Mahgoub Hussien; Salim, Omer El faroug (Gezira Journal of Health Sciences; Vol 16 No 1 (2020), 2020)
Introduction : Worldwide breast cancer is the most common cancer among females, It is the leading cause of death in the developing countries. Diagnosis of breast cancer has major impact on women quality of life, especially with advances in treatment modalities and disease-free survival the number of young survivors increased. Objective: To assess quality of life in Sudanese patients diagnosed with breast cancer in Radiation and Isotopes Center, Khartoum. Materials and Methods: A descriptive cross sectional hospital based study Radiation and Isotopes Center, Khartoum. 167 patients diagnosed with breast cancer pre- operative and post-operative receiving chemotherapy were included and interviewed using the Arabic version of SF-36 Quality of life standard questionnaire. Analysis was done with SPSS version 25. Results : 52.7% were more than 50 years of age, 43.1% had low monthly income. 70.7% underwent surgical treatment, 29% of patients started first with chemotherapy. 55.1% underwent mastectomy and 15.6% underwent breast conserving surgery. The best score was for role limitation due to emotional health with 94.6% had good score (Mean 2.8 ,SD 0.45 ). The worst score was for role limitation due to physical health with 66.5% had bad score (Mean1.6 ,SD 0.9).Social activities was extremely affected in 31.1% of patients. There is no difference in quality of life between patients treated with mastectomy versus those treated with breast conserving surgery in all domains except for social functioning which is better for mastectomy patients (p. value is 0.01). Conclusion: The overall quality of life was within the average range for most domains of quality of life, but social functioning was extremely affected. So further studies are needed with inclusion of other centers with regular follow-up to assess change in pattern of quality of life over years. Patients should be enrolled in a social support groups for better outcome.